Accuracy of D-Dimer Levels and C-reactive Protein in Predicting Perforation of Acute Appendicitis - Gema Putra Lesmana; Reno Rudiman; Rani Septrina (Jurnal llmu Bedah Indonesia, 2020)
Introduction: D-Dimer as the primary product of fibrin degradation, was found to be increased in appendicitis patients. CRP still gives different results in predicting perforated appendicitis. The purpose of this study is to find out the accuracy of D-Dimer and CRP in predicting appendicitis perforation at the Central General Hospital Dr. Hasan Sadikin Bandung 2019. Method: This study used prospective observational design with cross-sectional approach. The subject were taken from the Emergency Department (ED) patient between September 2018-September 2019 who met the inclusion criteria. Preoperative D-Dimer and CRP serum were measured and the results of the surgery were noted. Chi-Square test was conducted and the data were analyzed using SPSS Version 22.0 for windows at a 95% confidence level. The value is significant if p <0.05. Results: The sample included in this study were 41 patients, with 24 perforated appendicitis patients. The average age of patients was 34.8 ± 13.8. The majority of patients were male, 24 patients ( 58.5%). Area for ROC curve for D-Dimer is 0.929, with a cut-off point of 0.51 mg / l for sensitivity perforation appendicitis 95.8%, specificity 76.5%, positive predictive value (PPV) 85.2%, negative predictive value (NPV) 92.9% and accuracy 87.8%. For CRP with a cut-off point at 18.84 for sensitivity perforation appendicitis 58.3%, specificity 94.1%, positive predictive value (PPV) 93.3%, negative predictive value (NPV) 61.5% with an accuracy of 73.2%. Conclusion: D-dimer and CRP level can be used in predicting perforation of appendicitis. (ISSN 2723-7494 J Bedah Indonesia. 2020;48:3-14)